On Complex Differential-Difference Equations of Malmquist Type - Jianjun Zhang (Journal of Mathematics)
In this paper, we shall give some properties of complex differential-difference equation of the form ∑μ=1nαμz∏i=1tfz+ciai0μf′z+ciai1μ⋯fkiz+ciaikiμ/∑ν=1mβνz∏i=1tfz+cibi0νf′z+cibi1ν⋯fkiz+cibikiν=Rz,fz, where aijμ μ=1,2,…,n and bijνν=1,2,…,mi=1,2,…,t;j=0,1,…,ki are non-negative integers, cii=1,2,…,t are distinct, nonzero complex numbers, αμzμ=1,2,…,n and βνzν=1,2,…,m are small functions relative to fz, and Rz,fz is a rational function in fz with coefficients, which are small functions of fz. We also consider related complex functional equations in the paper. These results are improvements of some several previous results.